Perkembangan dan Implikasi Teknologi Informasi dan Komunikasi dalam Pembelajaran di Sekolah Dasar: Tinjauan Naratif - Gunawan Gunawan; Baiq Nabila Saufika Zainuri; Lovy Herayanti; Fahmi Yahya (Indonesian Publication Center, 2021)
The integration of Information and Communication Technology (ICT) has profoundly transformed the landscape of primary education. This study aims to present a comprehensive narrative review mapping the developments and implications of ICT integration in primary schools based on national scientific literature published up to 2020. Employing a narrative review methodology, a total of 22 national journal articles were selected through systematic screening based on predefined inclusion and exclusion criteria. Data were analyzed using qualitative content analysis to synthesize major thematic trends. The findings reveal a significant evolutionary shift in educational media, moving from basic computer-assisted instruction to advanced interactive multimedia, digital platforms (such as Kahoot and Google Earth), and immersive technologies like Augmented Reality (AR). These innovations have demonstrated positive implications for enhancing student engagement, visual-spatial awareness, and abstract concept comprehension across various primary school subjects. However, macro-level implementation remains hindered by chronic infrastructure disparities and uneven teacher digital competence. The urgency of these challenges culminated in late 2020, when the COVID-19 pandemic forced a rapid transition to emergency remote learning. In conclusion, while ICT offers substantial pedagogical benefits, its sustainable success in primary education requires equitable infrastructure distribution and continuous professional development for teachers.